PENGARUH PENYULUHAN TERHADAP TINGKAT PENGETAHUAN IBU TENTANG STIMULASI PIJAT BAYI - Rosita, Siskana Dewi; Remedina, Gipfel (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
Baby massage stimulation is one of the early stimulation for the babies to optimalize their growth. There will be multisensory stimulation on the process of the massage, such as: visual on mothers’ eye contact, auditory on verbal communication, sense of smell, physical touch, and bonding affection. Baby massage stimulation is better done regularly, based on the correct order and technique, and performed by the babies’ parents. Health promotion is the strategy to develop people’s health level, through health counseling to mothers, we can identify the mothers’ knowledge level on baby massage stimulation. This research is intended to identify the effect of counseling to mothers’ knowledge level on baby massage stimulation. Quasi experiment using one group of pretest-posttest was used as the method of the research. The population of this research was 38 participants consist of mother having 1-12 months baby who come to Posyandu Balita Rukun Asih Surakarta. Sampling applied was purposive sampling to fulfill the criteria of inclusive and exclusive into 31 participants. The instrument used is questionnaire on the knowledge level on baby massage stimulation. The data were analyzed by using Univariat and Bivariat t-test on the level of p=0,05. The analyzing result shows the mean rank of the group before receiving counseling is 8,50 and to the group after receiving counseling is 12,16 with the value score 0,000. The research finding leads to the conclusion that there is an effect of counseling to mothers’ knowledge level on baby massage stimulation. Keywords: counseling, knowledge level, baby massage stimulation